Immigration process of White-spotted Bluethroat Luscinia svecica cyanecula in Western Sweden - Andersson, Reino (Ornis Svecica, 2022)
is the latest addition to the Swedish bird fauna, with the first breeding in Scania in 2015. There were only three records on the Swedish West Coast north of Scania through 2016 and the first breeding was reported in 2018. Censuses performed in 2020 and 2021 revealed 12 and 17 singing males, respectively. Out of 39 singing males 2017–2021, 36 were found in Halland. Most birds were found in coastal wetlands with reedbeds, to which they arrived mainly in April. Nine males represented breeding pairs and second clutches were later observed for four breeding pairs. The Swedish expansion should be seen in the context of Danish immigration in combination with a large-scale advance via the Netherlands and Germany. The White-spotted Bluethroat belongs to those range-expanding taxa that are expected to increase due to warmer climate. As there is plenty of appropriate habitats, not least rapeseed fields, the conditions favour a continued range expansion in southern Sweden.